Ramie Fiber-Reinforced Polylactic-Acid Prepreg: Fabrication and Characterization of Unidirectional and Bidirectional Laminates - Tresna Priyana Soemardi; Olivier Polit; Fanya Salsabila; Ardy Lololau (International Journal of Technology, 2023)
The fabrication of a natural prepreg with poly-lactic acid (PLA) matrix and ramie fiber reinforcement was engineered on a laboratory scale by impregnating the unidirectional and bidirectional ramie fiber with PLA matrix solvent on a glass die. The obtained composite prepreg has been stored at a very low temperature to maximize its shelf life. Tensile and biodegradability tests of the composite laminates prepared by the hot-pressing method have also been conducted. Tensile test results show that the freezer-stored bidirectional 0/90° prepreg laminate specimen has the highest tensile strength of 71.44 MPa with a modulus of 2.70 GPa on average. Meanwhile, the unstored bidirectional 0/90° prepreg laminate specimen has the highest level of elasticity, with a modulus of 1.29 GPa on average. The biodegradability test shows the decomposition process of the composite laminate under actual composting conditions. Microscopic observation of the damaged specimen results shows good adhesion between the PLA matrix and ramie fiber and the decomposition of the biodegradability test samples.